Successful business intelligence : secrets to making BI a killer app - Howson, Cindi (McGraw-Hill, 2007)
"In todays highly competitive global economy, actionable business intelligence (BI) is crucial to success. Yet while many companies have made substantial investments in BI infrastructure, few employees are taking advantage of the powerful BI tools they have at their fingertips. This is because technology is only part of a truly successful. company-wide HI strategy, Executive support, an analytic culture, and strong business-IT partnerships and collaboration are among the many other facets that make up a winning end-to-end BI initiative." "Written by industry analyst and HI consultant Cindi Howson, Successful BusinessI ntelligence: Secretsto Making HI a KillerApp reveals how to get the most value out of your BI investments. The book draws on exclusive survey data and real-world case studies of BI success stories at Continental Airlines, The Dow Chemical Company, Corporate Express, 1-800CONTACTS, and other companies to identify proven HI best practices you can put to use in your organization."--Jacket